OXYGEN FUGACITY DEPENDENCE OF OS SOLUBILITY IN HAPLOBASALTIC MELT - Fortenfant S.S.; Dingwell D.B.; Ertel-Ingrisch W.; Capmas F.; Birck J.L.; Dalpé C. (My University, 2006)
Os equilibrium solubilities were determined at 1350 °C over a wide range of oxygen fugacities (-12 < log fO2 < -7) applying the mechanically assisted equilibration technique (MAE) at 105 Pa (= 1 bar). Os concentrations in the glass samples were analysed using ID-NTIMS. Additional LA-ICP-MS and SEM analyses were performed to detect, visualize and analyse the nature and chemistry of "nanonuggets." Os solubilities determined range at a constant temperature of 1350 °C from 0.63 ± 0.04 to 37.4 ± 1.16 ppb depending on oxygen fugacity. At the highest oxygen fugacities, Os3+ can be confirmed as the main oxidation state of Os. At low oxygen fugacities (below log fO2 = -8), samples are contaminated by nanonuggets which, despite the MAE technique, were still not removed entirely from the melt. However, the present results indicate that applying MAE technology does reduce the amount of nanonuggets present significantly, resulting in the lowest Os solubility results reported to date under these experimental conditions, and extending the experimentally accessible range of fO2 for these studies to lower values. Calculated metal/silicate melt partition coefficients are therefore higher compared to previous studies, making Os more siderophile. Neglecting the as yet unknown temperature dependence of the Os metal/silicate melt partition coefficient, extrapolation of the obtained Os solubilities to conditions for core-mantle equilibrium, results in a DOsFeliq,∞/sil = 1.5 × 105, while metallic alloy/silicate melt partition coefficients range from 1.4 × 106 to 8.6 × 107, in agreement with earlier findings. Therefore DOsmet/sil remains too high by 2-4 orders of magnitude to explain the Os abundance in the Earth's mantle as result of core-mantle equilibrium during core formation. © 2005 Elsevier Inc. All rights reserved.